Hubungan antara Minat Belajar dan Kepercayaan Diri Anak Brokem Home di Sd Nengeri 064012 - Putri Handayani Telaumbanua; Mujahid Wahidin Saragih (Yayasan Literasi Sains Indonesia, 2023)
Field Work Practice Activities (PKL) are paired with MBKM (USU Partner Teaching Campus batch 2). The implementation of the Teaching Campus activities took approximately 4 months at UPT SD Negeri 064012 Jl. D.I Panjaitan no 189, Medan Petisah District, Medan City, North Sumatra, Ms. Kholila Hanum S.Pd as head of UPT. I was entrusted by the principal of SD NEGERI 064012 to be a class 1A teacher for approximately 4 months. However, in carrying out this teaching campus program, I experienced problems due to the location or the place where I taught 90% of the orphanage. broker home Orphanage. Most students in grade 1A have problems with broken homes, some students don't know whose parents are, divorced or orphans. I focus on broken home children. Broken home describes a family that is not intact, separated/divorced, occurrence of domestic violence (KDRT) and no longer living together. This greatly affects the mentality and behavior of students while studying. In carrying out this activity I created a learning atmosphere that was safe, comfortable and in accordance with the interests and talents of students such as telling stories to students, paying attention, being a storyteller for children and being able to understand what the child was feeling. provide enthusiasm and motivation to learn and learn while playing.